Management Methods of Human Resources (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Human resources management (HRM) is managing people in an organisation. It encompasses various activities, including human resources planning, recruiting, hiring, training, appraising, and compensating employees. In some organisations, it may also incorporate the payroll function.